O jardim de si: paisagens líricas de Claudia Roquette-Pinto - Guizzo, Antonio Rediver (2014)
The current research focused on reflections and analysis about Claudia Roquette-Pinto lyric, from the purpose that the work of art is composed by four dimensions, the writer, society, work and imaginary, engendered on a dialogue in which synthesis does not exist, but a complementary relation, an indissoluble junction of opposites. Using this perspective, this search scrutinize the writer s lyric, composed on a border zone between modern economic social order saturation, guided by the planned utilization of the resources and by nature domination, and the post-modern insurgency of an ecological order, that privileges the actual fruition of this resources. From this dualism, we delineate, as a general objective, to comprehend how the constitutive dimensions of the work of art guide and establish senses on the writer poetic work. In order to achieve the proposed objective, the research was sustained by theoretician purposes of Gilbert Durand figurative structuralism, and its unfoldings on Jean Burgos and Maria Thereza de Queiroz Guimarães Strongoli assertions; on body, society and alterity relation, investigated by Michel Maffesoli and Zygmunt Bauman; by Bakhtin and Edward Wilson questions about language and consciousness, also on subjectivity and literary work of Dominique Combe, Paul Ricoeur, Alfredo Bosi, Antonio Candido e Theodor Adorno. This research, thus, uses the bibliography method, by a perspective that dialogues with phenomenology, sociobiology and figurative structuralism, also taking into consideration some hermeneutical considerations, discipline that analyzed the lyric of Claudia Roquette-Pinto, contemporary poet. As a result of this investigation process, we intend to conciliate the resulting analysis of the four constitutive dimensions of the work of art, using the complementary principle (not excluding coexistence of the opposites), not searching a totalizing synthesis of the perceptions derived from the writer poetic, but the description of plural senses emanated of a poetic making that creates itself in an historical moment when different social orders coexist and multiple communities are established by an esthetics ethics